1997
DOI: 10.1111/j.1524-4725.1997.tb00670.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Mohs Micrographic Surgery and Wide Excision for the Treatment of Atypical Fibroxanthoma

Abstract: Microscopic control of the surgical margins with MMS in the treatment of AFX results in a lower recurrence rate than that with WE and conserves normal tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
125
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(130 citation statements)
references
References 17 publications
3
125
0
2
Order By: Relevance
“…Given the lack of certainty in diagnosis and the potential for recurrence or metastases, it has been suggested that MMS should be the preferred modality of treatment [7]. MMS offers the advantage of microscopic control of surgical margins, a lower recurrence rate than that with WLE and conserves normal tissue [21]. There is no general consensus on the duration of follow-up, however due to the possibility of recurrence, metastases and development of other skin malignancies, one review has suggested that patients diagnosed with AFX should undergo 6-monthly review [7].…”
Section: Discussionmentioning
confidence: 98%
“…Given the lack of certainty in diagnosis and the potential for recurrence or metastases, it has been suggested that MMS should be the preferred modality of treatment [7]. MMS offers the advantage of microscopic control of surgical margins, a lower recurrence rate than that with WLE and conserves normal tissue [21]. There is no general consensus on the duration of follow-up, however due to the possibility of recurrence, metastases and development of other skin malignancies, one review has suggested that patients diagnosed with AFX should undergo 6-monthly review [7].…”
Section: Discussionmentioning
confidence: 98%
“…6 The mainstay of treatment of the condition is local surgical excision, and the need for complete excision in the management has been emphasized. 8 Indeed, the importance of complete excision to help prevent recurrence has led some to the use of Moh's micrographic surgery, 9 and although some consider it the treatment of choice, 10 difficulties in establishing an accurate preoperative diagnosis are likely to limit such treatment. In our series, there has been no recurrence to date after this local excision.…”
Section: Discussionmentioning
confidence: 99%
“…A 1cm margin, including subcutaneous tissue up to muscle fascia, should be used if histological control of margins is not possible during surgery. 49 …”
Section: Treatmentmentioning
confidence: 99%